PEMBELAJARAN KONSEP NUMERASI BERBASIS MEDIA ULAR TANGGA - Amatullah, Nurul; Rahman, Abdul; Sari, Vernita (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
Community Service Activities were carried out at UPTD SD Negeri 1 Parepare involving 20 class III students and class teachers as assistants. This program aims to improve students' numeracy skills through the use of educational game media specifically designed to support understanding of basic mathematical concepts. The implementation method is divided into three stages, namely preparation, implementation and evaluation. In the preparation stage, observations of needs and design of numeration snake and ladder media were carried out. The implementation phase focuses on using game media as a learning tool through playing activities while answering numeracy questions. Next, the evaluation stage is carried out through observation, interviews and assessment of student learning outcomes. The results of the activity show that the snakes and ladders numeracy media has a positive impact on students' motivation, participation and understanding. As many as 90% of students were actively involved, indicating increased interest and enthusiasm for numeracy material. Learning becomes more interactive, fun, and can reduce students' boredom towards mathematics. In addition, teachers gained increased skills in using innovative learning media and expressed readiness to apply them in regular learning. Overall, the numeracy snakes and ladders media has been proven to be a simple and effective learning alternative for improving elementary school students' numeracy literacy and the quality of mathematics learning in schools.